2015
DOI: 10.1042/cs20140300
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations, HFE gene mutations and atherogenic lipoprotein modifications in patients with primary iron overload

Abstract: Iron overload (IO) has been associated with glucose metabolism alterations and increased risk of cardiovascular disease (CVD). Primary IO is associated with mutations in the HFE gene. To which extent HFE gene mutations and metabolic alterations contribute to the presence of atherogenic lipoprotein modifications in primary IO remains undetermined. The present study aimed to assess small, dense low-density lipoprotein (LDL) levels, chemical composition of LDL and high-density lipoprotein (HDL) particles, and HDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…On the contrary, iron depletion, the most common and effective treatment for IO patients, would decrease low-density lipoprotein (LDL) oxidation and increase high-density lipoprotein cholesterol (HDL-C) levels [ 13 ]. Consistently, prior studies carried out by our group showed that HDL from IO patients present both quantitative and qualitative alterations associated with higher risk of cardiovascular disease [ 14 , 15 ].…”
Section: Introductionsupporting
confidence: 88%
“…On the contrary, iron depletion, the most common and effective treatment for IO patients, would decrease low-density lipoprotein (LDL) oxidation and increase high-density lipoprotein cholesterol (HDL-C) levels [ 13 ]. Consistently, prior studies carried out by our group showed that HDL from IO patients present both quantitative and qualitative alterations associated with higher risk of cardiovascular disease [ 14 , 15 ].…”
Section: Introductionsupporting
confidence: 88%
“…Given that in the present study we observed higher prevalence of impaired fasting glucose and of overweight and obesity, an increase of IL-17 could be expected. Moreover, several studies had shown the wide spectrum of metabolic alterations that may be present in primary IO patients [21][22][23]. Therefore, inflammatory cells could be a relevant source of IL-17 in patients with primary IO and metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated iron levels exacerbate hyperlipidemia and hyperglycemia in animal models, including zebrafish, rats, mice as well as humans ( 35 , 120 , 137 , 164 , 232 ). Likewise, iron-loaded patients with HH show elevated cholesterol and hypertriglyceridemia ( 141 , 204 , 232 ), which can be improved by therapeutic phlebotomy ( 37 , 232 ). Conversely, iron deficiency is associated with significantly lower hepatic cholesterol content and reduced serum total cholesterol, LDL, and triglyceride levels in rodents and men ( 47 , 51 , 138 , 207 , 227 ).…”
Section: Current Molecular Mechanisms Of Iron-mediated Vasculotoxicitymentioning
confidence: 99%